Experimental Investigation of Two- and Three-Blade Savonius Hydrokinetic Turbine for Hydropower Applications: A Study across Various Turbine Positions from Channel Centre to Channel Wall - Shanegowda Tharedakuppe Gangashanaiah; Shashikumar C M; Veershetty Gumptapure; Vasudeva Madav (Engineering Proceedings)
Hydrokinetic energy has gained significant attention in recent years as a promising renewable energy source due to its low environmental impact and potential for use in remote locations. This research aims to optimize the performance of the Savonius hydrokinetic turbine, a crucial component of zero-head hydropower systems, for efficient renewable energy extraction from flowing water. Laboratory-scale experiments with two and three-blade Savonius turbines at different channel positions investigate geometric dimensions and design parameters like the power coefficient (CP) and Torque coefficient (CT). The experimental results are compared with previous research, confirming the superiority of the two-blade configuration, which achieved CP and CT at the same TSR and channel locations. Specifically, the two-blade Savonius turbine demonstrated a CP of 0.27 and a CT of 0.37 at TSR 0.7 and the channel’s centre placement. Placing the turbine at the channel centre yields the best performance for both configurations. This study provides valuable insights for enhancing the efficiency of hydrokinetic turbines, contributing to renewable energy technology advancements, and addressing climate change and energy security challenges. The Savonius hydrokinetic turbine has the potential to be a sustainable energy source.